2005
DOI: 10.1111/j.1471-0528.2005.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Female sterilisation: a cohort controlled comparative study of ESSURE versus laparoscopic sterilisation

Abstract: Objective To compare patient satisfaction, discomfort, procedure time, success rate and adverse events of hysteroscopic (ESSURE, Conceptus Inc, San Carlos, USA) versus laparoscopic sterilisation. Design Cohort controlled comparative study.Setting The day surgery and outpatient unit of three large UK hospitals.Population Eighty-nine women requesting sterilisation were enrolled into the study.Methods A 2:1 ratio of ESSURE placement to laparoscopic sterilisation was undertaken. Laparoscopic sterilisation was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 7 publications
(14 reference statements)
5
61
0
6
Order By: Relevance
“…A high insertion success rate appears to be related to the hysteroscopist's experience, good technique and with the use of oral contraceptives and NSAIDs prior to the procedure. Essure tubal sterilisation is a favourable replacement for laparoscopic tubal occlusion 8 as it is less invasive, can be performed without hospital admission and has a low rate of failure and complications. The insertion is quick and well tolerated, and it permits a rapid return to normal activity producing a very high degree of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A high insertion success rate appears to be related to the hysteroscopist's experience, good technique and with the use of oral contraceptives and NSAIDs prior to the procedure. Essure tubal sterilisation is a favourable replacement for laparoscopic tubal occlusion 8 as it is less invasive, can be performed without hospital admission and has a low rate of failure and complications. The insertion is quick and well tolerated, and it permits a rapid return to normal activity producing a very high degree of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…81 Hysteroscopic sterilization is less invasive than traditional laparoscopic techniques, presumably leading to a lower risk of serious complications. 82 Hysteroscopic tubal occlusion is advantageous for many older women who may not be good candidates for laparoscopic tubal sterilization because of intra-abdominal adhesions, medical comorbidities or obesity. 82 …”
mentioning
confidence: 99%
“…82 Hysteroscopic tubal occlusion is advantageous for many older women who may not be good candidates for laparoscopic tubal sterilization because of intra-abdominal adhesions, medical comorbidities or obesity. 82 …”
mentioning
confidence: 99%
“…As more physicians adopt the Essure method for sterilization, they continue to look for techniques to improve the rate of successful bilateral coil placement on the first attempt. The reported bilateral placement rate ranges from 81% [1] to 98% [2]. It has been suggested that the procedure be completed in the follicular phase to improve visualization of the tubal ostia, and thus the successful placement of the coils [3][4][5].…”
Section: Introductionmentioning
confidence: 97%